STATE AND PROSPECTS OF ELECTRIC POWER SOURCES OF AVIATION POWER SUPPLY SYSTEMS (Archive of Conferences, 2021)
The article suggests the use of contactless electric machines as primary sources of elec-tricity in on-board power supply systems: synchronous generators with excitation from per-manent magnets and asynchronous generators with capacitive excitation